Sosialisasi Pemilahan Sampah Organik dan Anorganik untuk Menjaga Lingkungan yang Berdampak bagi Kesehatan dan Ekonomi: Sosialisasi Pemilahan Sampah Organik dan Anorganik untuk Menjaga Lingkungan yang Berdampak bagi Kesehatan dan Ekonomi (Jumat Pendidikan: Jurnal Pengabdian Masyarakat, 2023)
The purpose of this community service activity is to overcome problems and provide an understanding of protecting the environment and implementing the segregation of organic and inorganic waste. Based on the description of the situation analysis and taking into account the problems faced by the service partners, it can be seen that the focus of the service partner's problem lies in the lack of knowledge about keeping the environment clean, especially garbage disposal, and the lack of supporting facilities. To overcome this, his dedication is trying to overcome the problem through socialization activities for sorting organic and inorganic waste disposal in the importance of keeping the environment clean and helping to provide trash facilities. The success of the Community Partnership Program socializing the sorting of organic and inorganic waste requires support from related parties, namely the proposer (KH. A. Wahab Hasbullah University) and students of the Tanwirul Qulub Islamic Boarding School. Measuring the results of the achievement of community service activities can be observed from the achievement of the goals and targets that have been planned. After the community service activities were carried out, the participants experienced an increase in information and insight in determining organic and inorganic waste and disposing of it according to the criteria. Where the development of community service activities is able to create a clean Islamic boarding school environment. The outputs achieved include students being able to protect the environment and implement the segregation of organic and inorganic waste. Because sorting organic and inorganic waste can have an impact on health and also the economy. The health impacts include avoiding the dangers of disease while the economic impacts can be used as compost, animal feed (organic waste) and can also recycle used goods into useful goods (inorganic waste), thereby helping to reduce expenses. Suggestions for community service partners are that partners must always keep the environment clean, partners must be good at sorting organic and inorganic waste.